(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives:(1) To describe the epidemiological characteristics, habits, clinical and paraclinical features of patients with osteoporosis at the Musculoskeletal Center, Vo Truong Toan University Hospital.(2) To identify several risk factors associated with the severity of osteoporosis among both inpatient and outpatient populations. Subjects and Methods:A cross-sectional descriptive study with analytical elements was conducted on 115 patients diagnosed with osteoporosis from January to June 2025. A total sampling method was applied. Data were collected through direct interviews and medical record reviews, and analyzed using SPSS version 22.0. Results:The study included 115 patients, with a predominance of females (82.6%), mainly aged between 50 and 70 years (63.5%), and the majority engaged in manual labor (91.3%).Clinically, the most common symptom was bone pain (89.6%), followed by back pain (88.7%), and knee pain/fatigue (73%). Neck and shoulder pain had the lowest prevalence (26.1%).Statistical analysis showed a significant association between bone pain and severe osteoporosis (T-score ≥ -3.5 SD), with p = 0.023. Interestingly, patients who did not consume alcohol had a higher rate of severe osteoporosis compared to those who did, with p = 0.003. Additionally, the longer the disease duration, the higher the rate of severe osteoporosis — notably, 50% of patients with a disease duration over 10 years had severe osteoporosis (p = 0.01). Conclusion:Osteoporosis tends to be more prevalent in females, individuals of middle age or older, particularly those involved in manual labor, with obesity, sedentary lifestyle, or comorbid chronic diseases. Early screening and interventions should be strengthened for high-risk populations.